VD_FINDINFO HC / 2016 / 945 vom 20. September 2016 - VD Tribunal cantonal (2016)
MESURE PROVISIONNELLE, CAUSE DE DIVORCE, DIVORCE, OBLIGATION D'ENTRETIEN, ENFANT | 163 al. 1 CC, 179 al. 1 CC, 276 CPC (CH)